Analysis of heat shock protein 70 gene polymorphisms Mexican patients with idiopathic pulmonary fibrosis. Issue 1 (December 2015) - Aquino-Gálvez, Arnoldo; González-Ávila, Georgina; Pérez-Rodríguez, Martha; Partida-Rodríguez, Oswaldo; Nieves-Ramírez, Miriam; Piña-Ramírez, Inocencio; Ramírez-Martínez, Gustavo; Castillejos-López, Manuel; Checa, Marco; Ruiz, Victor; Urrea, Francisco; Sommer, Bettina; et al.
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease of unknown etiology. Genetic variation within different major histocompatibility complex (MHC) loci contributes to the susceptibility to IPF. The effect of 70 kDa heat shock proteins (HSP70 ) gene polymorphisms in the susceptibility to IPF is unknown. The aim of this study was to explore the association between HSP70 polymorphisms and IPF susceptibility in the Mexican population. Methods Four HSP70 single nucleotide polymorphisms (SNPs) were evaluated using real time PCR assays in 168 IPF patients and 205 controls: +2763 C>T ofHSPA1L (rs2075800), +2437 ofHSP HSPA1L A>G (rs2227956), +190 ofHSPA1A G>C (rs1043618) and +1267 ofHSPA1B G>A (rs1061581). Results The analysis of the recessive model revealed a significant decrease in the frequency of the genotype HSPA1B AA (rs1061581) in IPF patients (OR = 0.27, 95 % CI = 0.13–0.57, Pc = 0.0003) when compared to controls. Using a multivariate logistic regression analysis in a codominant model theHSPA1B (rs1061581) GA and AA genotypes were associated with a lower risk of IPF compared with GG (OR = 0.22, 95 % CI = 0.07–0.65;p  = 0.006 and OR = 0.17, 95 % CI = 0.07–0.41;p  = <0.001). Similarly, HSPA1L (rs2227956) AG genotype (OR = 0.34, 95 % CI = 0.12–0.99;p  = 0.04) and the dominant model AG + GG genotypes were also associated with a lower risk of IPF (OR = 0.24, 95 % CI = 0.08–0.67;p  = 0.007). In contrast, theHSPA1L (rs2075800) TT genotype was associated with susceptibility to IPF (OR = 2.52, 95 % CI = 1.32–4.81;p  = 0.005). Conclusion Our findings indicate that HSPA1B (rs1061581), HSPA1L (rs2227956) andHSPA1 (rs1043618) polymorphisms are associated with a decreased risk of IPF.